Endothelium-derived 6-nitrodopamine is the major mechanism by which nitric oxide relaxes the rabbit isolated aorta - Santos, Eric Xavier Dos; Britto-Júnior, José; Ribeiro, João Victor; Junior, Gilberto Quirino; Lima, Antonio Tiago; Moraes, Manoel Odorico; Moraes, Maria Elisabete A.; Antunes, Edson; Schenka, André; De Nucci, Gilberto (Frontiers in Pharmacology, 2024)
6-Nitrodopamine (6-ND) is the predominant catecholamine released from isolated vascular tissues in both mammals and reptiles, with its release being significantly reduced by the NO synthesis inhibitor, L-NAME. The vasorelaxation induced by 6-ND is unaffected by either L-NAME or the soluble guanylate cyclase (sGC) inhibitor, ODQ, indicating an alternative mechanism of action. The vasorelaxant effect appears to be mediated through selective antagonism of dopamine D2 receptors rather than traditional nitric oxide (NO)-mediated pathways. This study examined the basal release of 6-ND, dopamine, noradrenaline, and adrenaline, from the rabbit thoracic aorta by LC-MS/MS. Additionally, the effects of 6-ND and the dopamine receptor antagonist L-741,626 on relaxation responses and electric field stimulation (EFS) in aortic rings were assessed. Nitric oxide pathway inhibitors, including L-NAME, ODQ, and methylene blue, were utilized to involvement of this pathway in the 6-ND induced vasorelaxation. Concentration-response curves for norepinephrine, epinephrine, and dopamine were generated in the presence and absence of 6-ND and L-741,626. Rabbit isolated aorta presented basal release of endothelium-derived dopamine and 6-ND. 6-Nitrodopamine and L-741,626 induced concentration-dependent relaxations in endothelin-1 pre-contracted aortic rings. The relaxations were reduced by mechanical removal of the endothelium, but unaffected by pre-treatment with L-NAME, ODQ, or methylene blue. Pre-incubation with 6-ND significantly reduced dopamine-induced contractions, while noradrenaline and adrenaline induced contractions remained unchanged. The findings demonstrated that endothelium-derived 6-ND is the most potent endogenous relaxant of rabbit isolated aorta, the mechanism is independent of NO pathway and involved blockade of dopamine D2 receptors.